Absorbent body and hygienic material product

By optimizing the configuration of the non-woven fabric and water-absorbing polymer group in the absorber, the problem of hindering liquid diffusion after the water-absorbing polymer enters the non-woven fabric is solved, and absorber and sanitary material products with excellent absorption characteristics and thin absorption are achieved.

CN119836281APending Publication Date: 2025-04-15TORAY INDUSTRIES INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380064287.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-13
Filing Date
2023-08-28
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

After the water-absorbing polymer enters the nonwoven fabric, the existing absorber hinders the diffusion of liquid, resulting in insufficient absorption characteristics, and the correlation of the diffusion of liquids in each layer is not considered.

Method used

The absorber consisting of the first nonwoven fabric, the first water-absorbing polymer group, the second nonwoven fabric, the second water-absorbing polymer group and the third nonwoven fabric is used. By containing more than 60% of the hydrophilic fibers in the second nonwoven fabric, and fixing the water-absorbing polymer group in each layer, the liquid diffusion area ratio is optimized to improve the absorption characteristics.

Benefits of technology

It realizes a thin absorber and sanitary material product with excellent absorption characteristics, which can effectively absorb a large amount of liquid, reduce discomfort during wear and reduce the risk of liquid leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005300111620000261
    Figure BDA0005300111620000261
  • Figure BDA0005300111620000271
    Figure BDA0005300111620000271
  • Figure BDA0005300111620000281
    Figure BDA0005300111620000281
Patent Text Reader

Abstract

In order to make an absorbent body and a sanitary material product thin and to provide excellent absorption characteristics due to high utilization efficiency of an absorbent polymer disposed between nonwoven fabrics, the absorbent body of the present invention is formed from a configuration comprising a first nonwoven fabric, a first water-absorbent polymer group, a second nonwoven fabric, a second water-absorbent polymer group, and a third nonwoven fabric in this order, the absorbent body has a thickness of 4.0 mm or less, the first water-absorbent polymer group is fixed to the first non-woven fabric to form a first layer, the second water-absorbent polymer group is fixed to the third non-woven fabric to form a second layer, the second non-woven fabric contains hydrophilic fibers in an amount of 60% by mass or more with respect to the entire second non-woven fabric, and the thickness of the absorbent body is 4.0 mm or less. The liquid diffusion area of the first layer is 40-90 cm2, the value obtained by dividing the liquid diffusion area of the second non-woven fabric by the liquid diffusion area of the first layer is 1.1-2.0, and the value obtained by dividing the liquid diffusion area of the second non-woven fabric by the liquid diffusion area of the second layer is 1.1-2.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an absorbent body and a hygienic material product. Background Art

[0002] Sanitary products such as disposable diapers and sanitary napkins have a sheet-like absorbent body that absorbs aqueous liquids such as urine and menstrual blood (hereinafter sometimes referred to as urine, etc.) and retains water, a surface sheet arranged on one surface of the absorbent body, and a back sheet arranged on the other surface of the absorbent body. The surface sheet has the property of permeability to urine, etc., and the back sheet has the property of preventing urine, etc. from leaking. In addition, the absorbent body is formed by a mixture of pulp fibers and water-absorbing polymers wrapped with non-woven fabrics or paper towels, etc.

[0003] Furthermore, in the sanitary product, the absorbent body, the top sheet and the back sheet are arranged in this order from the top sheet, the absorbent body and the back sheet closer to the wearer when the sanitary product is worn.

[0004] Here, with the recent popularization of sanitary products such as disposable diapers and sanitary napkins, there is a demand for sanitary products to be thinner and have a better wearing feel. However, there is a problem that absorbent bodies using conventional pulp fibers become bulky and cannot be made thinner.

[0005] Therefore, as a thin absorbent without using pulp fibers in the absorbent, there is known an absorbent composed of a first nonwoven fabric, a first water-absorbing polymer group, a second nonwoven fabric, a second water-absorbing polymer group and a third nonwoven fabric in this order (for example, see Patent Document 1).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2019 / 198821 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, the inventors of the present invention have found that the conventional absorbent has the following problems. As mentioned above, the absorbent described in Patent Document 1 is an absorbent that does not use bulky pulp fibers in the absorbent, but is composed of a first nonwoven fabric, a first water-absorbent polymer group, a second nonwoven fabric, a second water-absorbent polymer group, and a third nonwoven fabric in this order. In addition, the absorbent uses a hot air nonwoven fabric in the second nonwoven fabric. However, the hot air nonwoven fabric has large gaps, and the water-absorbent polymer easily enters the hot air nonwoven fabric. If the water-absorbent polymer that enters absorbs urine and swells, it hinders the liquid diffusivity of the hot air nonwoven fabric, and as a result, there is a problem that the absorption characteristics of the absorbent as a whole are insufficient. In addition, there is no consideration of the correlation between the liquid diffusivity of the first layer formed by the first nonwoven fabric and the first water-absorbent polymer group and the second layer formed by the third nonwoven fabric and the second water-absorbent polymer group and the liquid diffusivity of the second nonwoven fabric, and there is a problem that the absorption characteristics of the absorbent as a whole are insufficient.

[0011] Therefore, in view of the above circumstances, an object of the present invention is to provide an absorbent body and a sanitary product which are thin and have excellent absorption characteristics due to high utilization efficiency of an absorbent polymer disposed between nonwoven fabrics.

[0012] Solutions to Solve Problems

[0013] In order to solve the above-mentioned problems, the absorbent body and sanitary product of the present invention are as follows.

[0014] Right now,

[0015] (1) An absorbent body comprising, in this order, a first nonwoven fabric, a first water-absorbing polymer group, a second nonwoven fabric, a second water-absorbing polymer group, and a third nonwoven fabric, wherein the absorbent body has a thickness of 4.0 mm or less,

[0016] The first nonwoven fabric and the first water-absorbing polymer group form a first layer,

[0017] The third nonwoven fabric and the second water-absorbing polymer group form a second layer,

[0018] The first water-absorbing polymer group is directly or indirectly fixed to the first nonwoven fabric,

[0019] The second water-absorbing polymer group is directly or indirectly fixed to the third non-woven fabric,

[0020] The second nonwoven fabric contains 60% by mass or more of hydrophilic fibers relative to the entire second nonwoven fabric.

[0021] The liquid diffusion area of ​​the first layer is 40 to 90 cm 2 ,

[0022] The value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer is 1.1 to 2.0,

[0023] The value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer is 1.1 to 2.5.

[0024] (2) Preferably, the absorbent core according to (1) is characterized in that the hydrophilic fiber is a rayon fiber.

[0025] (3) Preferably, in the absorbent body according to (1) or (2), the second nonwoven fabric has a basis weight of 20 to 50 g / m 2 .

[0026] (4) Preferably, the absorbent body according to any one of (1) to (3) is characterized in that the first nonwoven fabric contains short fibers A having a single fiber strength of 0.15 N or more,

[0027] The content of the short fibers A is 5 to 40% by mass based on the entire first nonwoven fabric.

[0028] (5) Preferably, the absorbent body according to any one of (1) to (4) has a weight per unit area of ​​50 to 400 g / m 2 .

[0029] (6) The absorbent core according to any one of (1) to (5), wherein the saturated absorption capacity of the water-absorbing polymer contained in the second water-absorbing polymer group is preferably 25 to 70 g / g.

[0030] (7) Preferably, a sanitary product includes the absorbent according to any one of (1) to (6).

[0031] Effects of the Invention

[0032] According to the present invention, it is possible to provide a thin absorbent body and a sanitary product which are excellent in absorption properties. DETAILED DESCRIPTION

[0033] Hereinafter, embodiments of the present invention will be described in detail.

[0034] The absorbent of the present invention comprises, in order, a first nonwoven fabric, a first water-absorbent polymer group, a second nonwoven fabric, a second water-absorbent polymer group and a third nonwoven fabric, and the thickness of the absorbent is 4.0 mm or less. In addition, the first nonwoven fabric and the first water-absorbent polymer group form a first layer, the third nonwoven fabric and the second water-absorbent polymer group form a second layer, the first water-absorbent polymer group is directly or indirectly fixed to the first nonwoven fabric, and the second water-absorbent polymer group is directly or indirectly fixed to the third nonwoven fabric. In addition, the second nonwoven fabric contains more than 60% by mass of hydrophilic fibers relative to the entire second nonwoven fabric. In addition, the liquid diffusion area of ​​the first layer is 40 to 90 cm 2 , the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer is 1.1 to 2.0, and the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer is 1.1 to 2.5. Moreover, the absorbent of the present invention having all these characteristics is formed into a thin absorbent with excellent absorption characteristics.

[0035] The mechanism by which the above-mentioned effect can be obtained is presumed as follows. That is, the absorbent of the present invention has the following structure: it has a first nonwoven fabric, a first water-absorbing polymer group, a second nonwoven fabric, a second water-absorbing polymer group and a third nonwoven fabric in this order, the first nonwoven fabric and the first water-absorbing polymer group form a first layer, the third nonwoven fabric and the second water-absorbing polymer group form a second layer, the first water-absorbing polymer group is directly or indirectly fixed to the first nonwoven fabric, and the second water-absorbing polymer group is directly or indirectly fixed to the third nonwoven fabric, and further has the following characteristics: the liquid diffusion area of ​​the first layer is 40 to 90 cm 2 The value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer is 1.1 to 2.0, and the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer is 1.1 to 2.5.

[0036] By configuring such an absorbent body in such a manner that the first layer side becomes the wearer side of the sanitary material product, liquid such as urine penetrates into the absorbent body from the first layer side of the absorbent body and travels inside the absorbent body in the order of the first layer, the second nonwoven fabric, and the second layer. In such an absorbent body, by making the liquid diffusion area of ​​the second nonwoven fabric larger than the liquid diffusion area of ​​the first layer and the liquid diffusion area of ​​the second layer, the absorption characteristics of the absorbent body of the present invention become excellent. Here, the larger the value of the liquid diffusion area of ​​the layer or nonwoven fabric, the better the liquid diffusivity of the layer or nonwoven fabric. In addition, the liquid diffusivity of the layer or nonwoven fabric has a relationship of increase and decrease with the liquid absorption amount of the average passage time of the layer or nonwoven fabric. Here, the liquid absorption amount of the average passage time refers to the amount of liquid that can be absorbed by the layer or nonwoven fabric during the period when the liquid such as urine passes through the layer or nonwoven fabric.

[0037] That is, the liquid reaching the first layer of the absorbent is diffused to a certain extent inside the first layer along its surface direction, and is absorbed to a certain extent by the first layer. Then, the liquid not absorbed by the first layer reaches the second nonwoven fabric, and diffuses widely inside the second nonwoven fabric along its surface direction. Then, the liquid not absorbed by the second nonwoven fabric is mostly transferred to the second layer, and the remaining liquid is transferred to the first layer. Here, the liquid transferred from the second nonwoven fabric to the first and second layers is fully diffused inside the second nonwoven fabric and then transferred, so the transfer is performed in a wide area of ​​the first and second layers. Thus, even if the liquid diffusivity of the first and second layers is worse than that of the second nonwoven fabric, the transferred liquid also reaches the entire water-absorbing polymer group that is spread along the surface direction of the first and second layers roughly evenly. Therefore, the water-absorbing polymers of the first and second layers can be effectively utilized. On the other hand, according to the above, since the liquid diffusivity of the first layer and the second layer can be lower than the liquid diffusivity of the second nonwoven fabric, the liquid absorption amount per average transit time of the first layer and the second layer can be increased instead.

[0038] That is, according to these characteristics of the absorbent body of the present invention, the absorbent body of the present invention can absorb a large amount of liquid, that is, it is excellent in absorption characteristics.

[0039] Here, in the first layer and the second layer, the water-absorbent polymer group is directly or indirectly fixed to the first nonwoven fabric or the second nonwoven fabric, so that in the absorbent body, the amount of absorbent polymer present in the second nonwoven fabric is extremely small. As a result, high liquid diffusivity of the second nonwoven fabric can be ensured.

[0040] Furthermore, the second nonwoven fabric contains 60% by mass or more of the hydrophilic fibers based on the entire second nonwoven fabric, which also contributes to high liquid diffusivity of the second nonwoven fabric.

[0041] As described above, since the absorbent of the present invention has high absorption characteristics, it is not necessary to contain bulky pulp fibers for ensuring high absorption characteristics, and as a result, a thin absorbent with a thickness of 4.0 mm or less can be made.

[0042] (1st to 3rd nonwoven fabric)

[0043] The first to third nonwoven fabrics included in the absorbent body of the present invention will be described.

[0044] Here, as the fibers constituting the first to third nonwoven fabrics, there can be mentioned olefin fibers such as polyethylene fibers and polypropylene fibers, polyester fibers such as polyethylene terephthalate fibers, polypropylene terephthalate fibers, and polybutylene terephthalate fibers, acrylic fibers such as nylon fibers and acrylonitrile fibers, and cellulose fibers such as cotton, linen, and rayon fibers. Among them, hydrophilic fibers are preferred, and rayon fibers that are excellent in liquid diffusivity such as urine and are easily fined are more preferred. In addition, from the viewpoint of liquid diffusivity such as urine, the first to third nonwoven fabrics preferably contain rayon fibers in an amount of 50% by mass or more relative to the entirety of each nonwoven fabric.

[0045] The first to third nonwoven fabrics preferably have a weight per unit area of ​​20 to 50 g / m 2 The weight per unit area of ​​the first to third nonwoven fabrics is more preferably 30 g / m2 because the water-absorbing polymer can be reliably supported by reducing the uneven weight per unit area of ​​the nonwoven fabric and the diffusion of liquid such as urine into the nonwoven fabric can be improved by increasing the number of fibers. 2 On the other hand, the weight per unit area of ​​the first to third nonwoven fabrics is more preferably 45 g / m2 because it is possible to suppress a decrease in the water permeability of urine or the like to the nonwoven fabric. 2 the following.

[0046] In addition, as the types of the first to third nonwoven fabrics, specifically, thermal bonded nonwoven fabrics, spunbonded nonwoven fabrics, and spunlace nonwoven fabrics can be cited. Among these, the first to third nonwoven fabrics are preferably spunlace nonwoven fabrics because they can be made into nonwoven fabrics without a binder, can suppress the risk of foreign matter such as needles being mixed in, and are more suitable for sanitary materials.

[0047] Furthermore, the first to third nonwoven fabrics included in the absorbent body of the present invention may be the same as or different from each other.

[0048] (No. 1 nonwoven fabric)

[0049] The first nonwoven fabric used in the absorbent core of the present invention will be described in detail.

[0050] Here, the first nonwoven fabric is arranged on the surface sheet side of the sanitary material, and urine etc. are quickly absorbed, and the urine etc. absorbed in the first nonwoven fabric is diffused, thereby increasing the water absorption of the first water-absorbing polymer group. From the viewpoint of being able to obtain the above-mentioned effect, the first nonwoven fabric preferably contains short fibers A having a single fiber strength of 0.15N or more, preferably contains 5 to 40% by mass of short fibers A relative to the entire first nonwoven fabric, and preferably contains 60 to 95% by mass of rayon fibers relative to the entire first nonwoven fabric. The fiber length of the short fibers A is preferably 20 to 80 mm, the raw material of the short fibers A is preferably polyester short fibers and polyamide short fibers, and the short fibers A are preferably hollow fibers.

[0051] In addition, the first nonwoven fabric preferably contains short fibers A having a single fiber strength of 0.15N or more, and preferably contains 5 to 40% by mass of short fibers A relative to the entire first nonwoven fabric. Short fibers refer to fibers having a fiber length in the range of 10 to 100 mm. From the perspective of the passability of the carding machine described later, the fiber length of the short fibers A is more preferably 20 to 80 mm. The single fiber strength of the short fibers refers to the maximum load of the elongation-load curve obtained when a tensile test is performed on one short fiber. More specifically, it refers to the value measured by the method described in the measurement method section of the embodiment. When manufacturing the first nonwoven fabric, even if a force that crushes the short fibers in the plane direction is applied by a water jet or a calender, the fiber axis of the entire first nonwoven fabric is easily oriented in the thickness direction due to the repulsion caused by the rigidity of the short fibers, thereby increasing the volume of the nonwoven fabric and increasing the voids of the nonwoven fabric. As a result, the absorption rate of urine or the like into the first nonwoven fabric can be accelerated. For the above reasons, it is more preferable that the first nonwoven fabric contains 10% by mass or more of the short fibers A relative to the entire first nonwoven fabric. On the other hand, it is more preferable that the first nonwoven fabric contains 35% by mass or less of the short fibers A relative to the entire first nonwoven fabric because it is possible to suppress a decrease in the liquid diffusibility of urine or the like into the first nonwoven fabric and a decrease in the softness that affects the wearing feeling of the sanitary product.

[0052] In addition, as the raw material of the short fiber A, there can be mentioned polyolefin short fibers such as polyethylene and polypropylene, polyester short fibers such as polyethylene terephthalate, polypropylene terephthalate, and polybutylene terephthalate, polyamide short fibers, and acrylic fibers such as acrylonitrile. Among these short fibers, polyester short fibers and polyamide short fibers are preferred because of their excellent strength, handling properties, and productivity. Furthermore, polyethylene terephthalate short fibers and nylon 6 and nylon 66 short fibers are more preferred.

[0053] The short fibers A are preferably hollow fibers. By forming hollow fibers, the short fibers A themselves become larger in volume, and the fiber axis of the entire first nonwoven fabric is easily oriented in the thickness direction, resulting in an increased absorption rate of the first nonwoven fabric and improved absorption properties of the absorbent.

[0054] Next, it is preferred that the first nonwoven fabric contains 60 to 95% by mass of rayon fibers relative to the entire first nonwoven fabric. From the reason that liquid diffusion of urine or the like into the nonwoven fabric is good, it is more preferred that the first nonwoven fabric contains 65% or more by mass of rayon fibers relative to the entire first nonwoven fabric. On the other hand, from the reason that water permeability can be improved by combining with the above-mentioned short fibers A of 0.15N or more, it is more preferred that the first nonwoven fabric contains 90% or less by mass of rayon fibers relative to the entire first nonwoven fabric.

[0055] (No. 2 nonwoven fabric)

[0056] Next, the second nonwoven fabric used in the absorbent body of the present invention will be described in detail. The second nonwoven fabric contains 60% by mass or more of hydrophilic fibers based on the entire second nonwoven fabric.

[0057] Here, the second nonwoven fabric is arranged between the first nonwoven fabric and the third nonwoven fabric, and by further taking into account the liquid diffusibility and water permeability of urine, etc. in the second nonwoven fabric, the water absorption amount in the water-absorbing polymer on the first nonwoven fabric side is increased, and the utilization efficiency of the water-absorbing polymer on the first nonwoven fabric side is improved. At the same time, by allowing urine, etc. to permeate to the third nonwoven fabric side, the water-absorbing polymer on the third nonwoven fabric side can be effectively utilized, and the absorption characteristics of the absorbent are excellent. From the viewpoint of being able to obtain the above-mentioned effects, the second nonwoven fabric contains 60% or more of hydrophilic fibers relative to the entire second nonwoven fabric, and the hydrophilic fibers are preferably rayon fibers. The unit weight of the second nonwoven fabric is preferably 20 to 50 g / m 2 .

[0058] In addition, the second nonwoven fabric contains 60% or more of hydrophilic fibers relative to the entire second nonwoven fabric. From the perspective of being able to improve the liquid diffusivity and water retention of the nonwoven fabric in urine, etc., it is preferred that the second nonwoven fabric contains 80% or more of hydrophilic fibers relative to the entire second nonwoven fabric, and more preferably 95% or more of hydrophilic fibers. As hydrophilic fibers, cellulose fibers such as cotton, linen, and rayon fibers can be cited. Among these, the hydrophilic fibers contained in the second nonwoven fabric are preferably rayon fibers because they are excellent in liquid diffusivity, easy to finely fine, and excellent in operability.

[0059] In addition, the three-dimensional arithmetic mean roughness of at least one side of the second nonwoven fabric is preferably 50 to 300 μm. The three-dimensional arithmetic mean roughness refers to the value of expanding the surface roughness parameter from two dimensions to three dimensions. More specifically, it refers to the value measured by the method described in the measurement method item of the embodiment. From the reason that the uneven loading of the water-absorbing polymer on the nonwoven fabric can be suppressed, the three-dimensional arithmetic mean roughness of at least one side of the second nonwoven fabric is more preferably 80 μm or more. On the other hand, from the reason that the liquid diffusivity of urine, etc. in the surface direction can be improved by smoothing the surface, the three-dimensional arithmetic mean roughness of at least one side of the second nonwoven fabric is more preferably 200 μm or less. In addition, as a method for making the three-dimensional arithmetic mean roughness of at least one side of the second nonwoven fabric within the above range, it is possible to cite the adjustment of the type of fibers constituting the nonwoven fabric, the unit area weight of the nonwoven fabric, the type of nonwoven fabric, the interlacing conditions when the nonwoven fabric is made, the method for making the mesh, the type of adhesive, the amount of adhesive used, etc.

[0060] (No. 3 nonwoven fabric)

[0061] The third nonwoven fabric used in the absorbent of the present invention is described in detail. The third nonwoven fabric allows urine and the like that have passed through the second nonwoven fabric to further diffuse in the third nonwoven fabric, thereby increasing the amount of absorption in the second water-absorbing polymer group. From the viewpoint of being able to obtain the above-mentioned effect, the third nonwoven fabric preferably contains 80% by mass or more of rayon fibers relative to the entire third nonwoven fabric, and more preferably contains 95% by mass or more of rayon fibers. If the content of hydrophilic rayon fibers increases, the liquid diffusibility of urine and the like into the nonwoven fabric becomes better.

[0062] (Methods for producing the first to third nonwoven fabrics)

[0063] Next, the method for producing the first to third nonwoven fabrics used in the absorbent of the present invention will be specifically described, but the method for producing the first to third nonwoven fabrics used in the absorbent of the present invention is not limited thereto. In addition, the methods for producing the first to third nonwoven fabrics may be different from each other.

[0064] The short fibers used to obtain the first to third nonwoven fabrics of the present invention are fed into a carding machine, mixed and opened, and then formed into a uniform web using a web forming machine. In the case where the first to third nonwoven fabrics of the present invention are spunlace nonwoven fabrics, the web is then fed into a water jet type nonwoven fabric forming device, and is entangled by high pressure water flow to form a nonwoven fabric. Then, the nonwoven fabric is dried in a hot air oven to obtain a spunlace nonwoven fabric.

[0065] In addition, from the reason that the utilization efficiency of the water-absorbing polymer is improved by improving the liquid diffusivity of urine or the like in the longitudinal direction in the rectangular absorbent, the above-mentioned mesh is preferably a parallel mesh (parallel mesh) in which the constituent fibers are oriented in the longitudinal direction, or a crisscross mesh (crisscross mesh) containing parallel meshes in which the constituent fibers are oriented in the longitudinal direction. In the nonwoven fabric obtained from these meshes, the fiber orientation degree of the constituent fibers in the longitudinal direction becomes high. It should be noted that the crisscross mesh is a material formed by stacking a cross mesh (cross mesh) in which the parallel meshes are oriented in the short side direction by cross-layering or the like and a parallel mesh.

[0066] (1st and 2nd water-absorbing polymer group)

[0067] The absorbent body of the present invention comprises a first water-absorbing polymer group and a second water-absorbing polymer group (hereinafter sometimes simply referred to as "water-absorbing polymer group"). The water-absorbing polymer group is composed of water-absorbing polymers.

[0068] Examples of the water-absorbing polymer used in the present invention include starch or cross-linked carboxymethyl cellulose, polymers of acrylic acid or alkali metal salts of acrylic acid or copolymers thereof, polyacrylic acid salts such as sodium polyacrylate, or polyacrylic acid salt graft polymers, etc. Among them, sodium polyacrylate is preferred from the viewpoint of productivity.

[0069] In addition, from the viewpoint of operability in the manufacturing process, etc., the water-absorbing polymer is preferably in a particle form. When the water-absorbing polymer is in a particle form, its particle size is preferably 50 to 800 μm. The particle size of the water-absorbing polymer is a diameter obtained by performing a circular approximation. More specifically, it refers to the value measured by the method described in the measurement method section of the embodiment. Here, by making the particle size of the water-absorbing polymer 50 μm or more, it is possible to inhibit: when the water-absorbing polymer is immersed in each of the first to third non-woven fabrics and the water-absorbing polymer after immersion absorbs / swells urine, etc., the liquid diffusivity of the non-woven fabric of urine, etc. is hindered. On the other hand, by making the particle size of the water-absorbing polymer 800 μm or less, it is possible to inhibit the reduction of the water absorption capacity of the water-absorbing polymer. As commercially available products of water-absorbing polymers having such a particle size, NS300 (particle size: 212-500 μm) manufactured by SDP GLOBAL, SA60S (particle size: 212-500 μm) manufactured by Sumitomo Seika, etc. can be cited.

[0070] The weight per unit area of ​​the first and second water-absorbing polymer groups is preferably 50 to 400 g / m 2 The weight per unit area of ​​the first and second water-absorbing polymer groups is more preferably 100 g / m2 because the absorption of urine or the like by the absorbent can be increased. 2 On the other hand, the weight per unit area of ​​the first and second water-absorbing polymer groups is more preferably 300 g / m2 because it can suppress the decrease in air permeability when used in sanitary products or suppress the leakage of the water-absorbing polymer absorbed by urine from the absorbent due to its weight. 2 the following.

[0071] In addition, the weight ratio of the first water-absorbing polymer group to the second water-absorbing polymer group is preferably 20:80 to 45:55. It is known that when water-absorbing polymers are densely present and come into contact with urine or the like, the water-absorbing polymers that have absorbed water and swelled come into contact with each other, thereby causing a gel blocking phenomenon that prevents other water-absorbing polymers that have not absorbed water or swelled from coming into contact with the aqueous liquid. However, by setting the weight ratio of the first water-absorbing polymer group to the second water-absorbing polymer group to the above range, urine or the like absorbed in the second water-absorbing polymer group can be prevented from returning to the first water-absorbing polymer group and the second nonwoven fabric, and the gel blocking phenomenon can be suppressed, resulting in improved absorption characteristics of the entire absorbent body. From the above viewpoint, the weight ratio of the first water-absorbing polymer group to the second water-absorbing polymer group is more preferably 30:70 to 40:60.

[0072] In addition, the gel permeation rate of the water-absorbing polymer contained in the first water-absorbing polymer group is preferably 50 to 350 ml / min. The gel permeation rate refers to the speed at which physiological saline passes through the water-absorbing polymers swollen and gelled by the physiological saline under load. More specifically, it refers to the value measured by the method described in the measurement method section of the embodiment. From the reasons that the liquid diffusivity of urine, etc. in the first water-absorbing polymer group can be improved, the amount of liquid delivered to the second non-woven fabric side of urine, etc. can be increased, and the absorption position when used in sanitary material products such as diapers can be improved, the gel permeation rate of the water-absorbing polymer contained in the first water-absorbing polymer group is more preferably 100 ml / min or more. On the other hand, from the reasons that the leakage of liquid such as urine from the first layer containing the first water-absorbing polymer group when the absorption of the first water-absorbing polymer is insufficient can be suppressed, the gel permeation rate of the water-absorbing polymer contained in the first water-absorbing polymer group is more preferably 250 ml / min or less.

[0073] In addition, the saturated absorption capacity of the water-absorbing polymer contained in the second water-absorbing polymer group is preferably 25 to 70 g / g. The saturated absorption capacity is a value measured by the tea bag method specified in JIS K 7223 (1996). More specifically, it refers to a value measured by the method described in the measurement method section of the examples. From the reason that the absorption characteristics of the absorbent body can be improved, the saturated absorption capacity of the water-absorbing polymer contained in the second water-absorbing polymer group is more preferably 30 g / g or more, and further preferably 35 g / g or more. On the other hand, from the reason that the water-absorbing polymer itself can be prevented from leaking out of the absorbent body due to the inability to maintain the shape of the absorbent body, the saturated absorption capacity of the water-absorbing polymer contained in the second water-absorbing polymer group is more preferably 60 g / g or less.

[0074] The water-absorbing polymer contained in the second water-absorbing polymer group preferably contains spherical particles or agglomerates of spherical particles, and contains 60% by mass or more of the spherical particles or agglomerates of spherical particles relative to the entire water-absorbing polymer contained in the second water-absorbing polymer group. From the reasons that it is possible to suppress the liquid such as urine from being sent to the third nonwoven fabric and to suppress the liquid such as urine from leaking from the third nonwoven fabric when the absorption of the first water-absorbing polymer and the second water-absorbing polymer is insufficient, it is more preferable that the spherical particles or agglomerates of spherical particles are contained at a rate of 80% by mass or more, and even more preferably at a rate of 95% or more, relative to the entire water-absorbing polymer contained in the second water-absorbing polymer group.

[0075] (Absorber)

[0076] The absorbent of the present invention comprises, in order, a first nonwoven fabric, a first water-absorbing polymer group, a second nonwoven fabric, a second water-absorbing polymer group and a third nonwoven fabric, and has a thickness of 4.0 mm or less. In addition, the first nonwoven fabric and the first water-absorbing polymer group form a first layer, and the third nonwoven fabric and the second water-absorbing polymer group form a second layer. In addition, the first water-absorbing polymer group is directly or indirectly fixed to the first nonwoven fabric, and the second water-absorbing polymer group is directly or indirectly fixed to the third nonwoven fabric. Furthermore, the liquid diffusion area of ​​the first layer is 40 to 90 cm 2 The value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer is 1.1 to 2.0, and the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer is 1.1 to 2.5.

[0077] The absorbent of the present invention comprises a first nonwoven fabric, a first water-absorbing polymer group, a second nonwoven fabric, a second water-absorbing polymer group, and a third nonwoven fabric in this order. With such a configuration, when the absorbent of the present invention is used in sanitary products such as diapers, urine or the like produced by the wearer quickly penetrates into the interior of the absorbent and is quickly absorbed by the water-absorbing polymer and retains water. Therefore, a sanitary product can be made that does not cause discomfort when worn and has little leakage of liquid such as urine.

[0078] Here, the thickness of the absorbent of the present invention is 4.0 mm or less. By making the thickness of the absorbent 4.0 mm or less, when the absorbent of the present invention is used in sanitary products such as diapers, the sanitary products using the absorbent of the present invention become soft, the roughness can be suppressed, and the wearing feeling can be excellent. From the reason of making the wearing feeling of the sanitary products better, the absorbent is preferably thin, and the thickness of the absorbent is preferably 3 mm or less. On the other hand, from the reason of making the absorption characteristics of the absorbent more excellent, the thickness of the absorbent is preferably 1 mm or more. It should be noted that the thickness of the absorbent mentioned here refers to the value measured based on JIS L1913 (1998) 6.1.2A method.

[0079] In addition, in the absorbent of the present invention, the first nonwoven fabric and the first water-absorbing polymer group form the first layer, and the third nonwoven fabric and the second water-absorbing polymer group form the second layer. In addition, the first water-absorbing polymer group is directly or indirectly fixed to the first nonwoven fabric, and the second water-absorbing polymer group is directly or indirectly fixed to the third nonwoven fabric. Hereinafter, the "first layer formed by the first nonwoven fabric and the first water-absorbing polymer group" may be simply referred to as the "first layer". In addition, the "second layer formed by the third nonwoven fabric and the second water-absorbing polymer group" may be simply referred to as the "second layer". Here, when the absorbent of the present invention is used for a sanitary material product, the first layer side becomes the use surface on the skin side, and the second layer side becomes the opposite side of the use surface on the skin side.

[0080] Here, the liquid diffusion area of ​​the first layer is 40 to 90 cm 2 . The so-called liquid diffusion area refers to the diffusion area of ​​physiological saline on the surface of the first nonwoven fabric side in the vertical direction from the first nonwoven fabric to the third nonwoven fabric of the absorbent body after 5 ml of physiological saline has passed from the surface of the first nonwoven fabric side to the other surface in the vertical direction from the first nonwoven fabric to the third nonwoven fabric. More specifically, it refers to the value measured by the method described in the measurement method section of the embodiment. The liquid diffusion area of ​​the first layer is preferably 45 cm because it can improve the liquid diffusivity of urine, etc. in the second nonwoven fabric connected to the first layer in the absorbent body, and can also improve the absorption efficiency of urine, etc. of the first water-absorbing polymer forming the first layer, and can also improve the absorption amount of urine, etc. of the first nonwoven fabric itself forming the first layer, so that the absorption characteristics of the absorbent body as a whole can be excellent. 2 More than 50 cm, more preferably 2 On the other hand, the liquid diffusion area of ​​the first layer is more preferably 85 cm2 because it can suppress the decrease in water permeability to the second nonwoven fabric and suppress the leakage of liquid from the first layer such as urine. 2 Below, more preferably 80cm 2 In addition, as a method for making the liquid diffusion area of ​​the first layer within the above range, there can be cited adjustment of the type of fibers constituting the first nonwoven fabric, the basis weight of the first nonwoven fabric, the type of the first nonwoven fabric, the entanglement conditions in the first nonwoven fabric, the method for preparing the first web, the type of the first water-absorbing polymer, the particle size of the first water-absorbing polymer, the basis weight of the first water-absorbing polymer group, the gel permeation rate of the first water-absorbing polymer, the type of adhesive, the amount of adhesive used, and the like.

[0081] Next, the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer is 1.1 to 2.0, and the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer is 1.1 to 2.5. By setting the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer to 1.1 to 2.0, and the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer to 1.1 to 2.5, the following adjustments can be made: the liquid such as urine diffused through the inside of the second nonwoven fabric can penetrate into the first layer and the second layer, thereby improving the absorption efficiency of urine and the like by the first water-absorbent polymer of the first layer and the second water-absorbent polymer of the second layer, or the leakage of liquid such as urine from the first layer when the absorption in the second water-absorbent polymer of the second layer is insufficient, or the leakage of liquid such as urine from the second layer when the absorption in the first water-absorbent polymer of the first layer is insufficient, etc., so that the absorption characteristics of the absorbent body can be excellent. From the viewpoint of being able to obtain the above-mentioned effects, the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer is preferably 1.2 or more, and preferably 1.8 or less. In addition, the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer is preferably 1.4 or more, and preferably 2.0 or less. Furthermore, since the liquid flows from top to bottom due to gravity, the amount of liquid transferred from the second nonwoven fabric to the second layer is greater than the amount of liquid transferred from the second nonwoven fabric to the first layer. Therefore, by making the liquid diffusion area of ​​the first layer larger than the liquid diffusion area of ​​the second layer, the absorption characteristics of the absorbent of the present invention become more excellent. Based on the above reasons, the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer is more preferably 1.3 or more, and more preferably 1.5 or less. In addition, the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer is more preferably 1.6 or more, and more preferably 1.8 or less. In addition, as a method for making the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer, and the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer within the above range, there can be cited adjustment of the type of fibers constituting the nonwoven fabric, the basis weight of the nonwoven fabric, the type of nonwoven fabric, the entanglement conditions in the nonwoven fabric, the method for preparing the web, the type of water-absorbing polymer, the particle size of the water-absorbing polymer, the basis weight of the water-absorbing polymer group, the gel permeation rate of the first water-absorbing polymer, the saturated absorption capacity of the second water-absorbing polymer, the shape of the second water-absorbing polymer, the type of adhesive, the amount of adhesive used, and the like.

[0082] In addition, as a material for fixing the water-absorbing polymer group required for forming the first layer and the second layer on the non-woven fabric, hot melt adhesives and heat-fusible resin powders can be cited. As the hot melt adhesive, a styrene-based hot melt adhesive or an olefin-based hot melt adhesive suitable for use in sanitary material products can be used as a suitable adhesive. In addition, as the heat-fusible resin powder, polyethylene powder and ethylene-vinyl acetate copolymer powder can be suitably used from the viewpoint of being able to perform heat fusion at a relatively low temperature. As a material for fixing the water-absorbing polymer group on the non-woven fabric, a hot melt adhesive is more preferably used because it can be fixed at a low weight per unit area.

[0083] The amount of hot melt adhesive applied to each of the first layer and the second layer is preferably 0.5 to 10.0 g / m 2 From the perspective of being able to fix the water-absorbing polymer on the nonwoven fabric, the amount of hot melt adhesive applied is more preferably 1.0 g / m 2 On the other hand, the amount of hot melt adhesive to be applied is more preferably 4.0 g / m2 because it can suppress the expansion inhibition of the water-absorbing polymer caused by hot melting. 2 Below, more preferably 3.0g / m 2 Below, particularly preferably 2.5 g / m 2 the following.

[0084] The absorbent body of the present invention is preferably in a substantially rectangular sheet shape, similarly to absorbent bodies used in known hygienic products such as diapers.

[0085] The absorption characteristic of the absorbent of the present invention preferably has an absorption capacity of 125 g or more. The absorption capacity in the present invention refers to the weight of the physiological saline absorbed by the absorbent when physiological saline is dripped in a 45° inclined state until the physiological saline leaks out from the lower end side of the sample. More specifically, it refers to the value measured by the method described in the measurement method item of the embodiment. By using the above-mentioned absorbent for sanitary material products, it can be formed into a material with excellent leakage prevention, which can inhibit leakage when the sanitary material product becomes an inclined state when taking a sleeping posture in the wearing state. From the above viewpoint, the absorption capacity of the absorbent is more preferably more than 150 g, and more preferably more than 175 g. As a means of obtaining such an absorbent, for example, the material described in Example 1 can be cited, and the manufacturing method described in Example 1 can be adopted. It should be noted that by appropriately adjusting one or more of the liquid diffusion area selected from the first layer, the liquid diffusion area of ​​the second nonwoven fabric, the liquid diffusion area of ​​the second layer, and the content of the hydrophilic fiber in the second nonwoven fabric, the absorption capacity of the absorbent can be within the above range.

[0086] (Method for producing absorbent body)

[0087] The method for producing the absorbent body of the present invention will be specifically described, but the method for producing the absorbent body of the present invention is not limited to the following method.

[0088] The absorbent body is obtained by fixing the water-absorbing polymer group between the first nonwoven fabric and the second nonwoven fabric, and between the second nonwoven fabric and the third nonwoven fabric. As a method for fixing the water-absorbing polymer group, the following method can be cited: (1) A hot melt adhesive is uniformly spread on one surface of the third nonwoven fabric in a spray or spiral shape. Then, the second water-absorbing polymer is uniformly spread thereon. Then, one surface of the second nonwoven fabric is pressed thereon. Then, the first water-absorbing polymer is uniformly spread on the other surface of the second nonwoven fabric (the surface not spread with the second water-absorbing polymer). In addition, a hot melt adhesive is sprayed or spirally spread on one surface of the first nonwoven fabric. Then, the other side of the second nonwoven fabric (the side on which the first water-absorbing polymer is sprinkled) is pressure-bonded to one side of the first nonwoven fabric (the side on which the hot-melt adhesive is sprinkled), or (2) a substance in which a heat-fusible resin powder and a first water-absorbing polymer are uniformly mixed in advance is sprinkled on one side of the first nonwoven fabric, and then the second nonwoven fabric is covered from the first water-absorbing polymer group, heated to a temperature above the melting point of the heat-fusible powder and heat-compression-bonded, and further, a substance in which a heat-fusible resin powder and a second water-absorbing polymer are uniformly mixed in advance is sprinkled on the other side of the second nonwoven fabric, and then the third nonwoven fabric is covered from the second water-absorbing polymer group, heated to a temperature above the melting point of the heat-fusible powder and heat-compression-bonded.

[0089] (Method for producing sanitary material products)

[0090] The manufacturing method of sanitary material products such as diapers and sanitary napkins using the absorbent of the present invention is described. The absorbent of the present invention cut into a rectangle is clamped and fixed between a surface sheet and a back sheet that are also rectangular and larger in area than the absorbent. It should be noted that the surface sheet side becomes the use surface of the skin side, and the back sheet becomes the surface on the opposite side of the use surface of the skin side. Here, it is preferred to clamp the absorbent with the surface sheet and the back sheet in a manner that the first nonwoven fabric of the absorbent is in contact with the surface sheet. Since the first nonwoven fabric has the characteristic that the aqueous liquid easily penetrates from one surface of the first nonwoven fabric to the other surface, by contacting the surface sheet with the first nonwoven fabric, the aqueous liquid that penetrates into the inside of the surface sheet quickly penetrates the first nonwoven fabric, and is easily absorbed and retained by the water-absorbing polymer. Therefore, the absorption characteristics of the absorbent can be improved. The method of fixing the surface sheet with the absorbent, the back sheet with the absorbent, and the surface sheet with the back sheet directly in contact can cite a method using a hot melt adhesive or a method using a heat-fusible resin powder.

[0091] In addition, as the surface sheet used when the absorbent of the present invention is made into a sanitary material product, from the viewpoint of better liquid permeability and touch, nonwoven fabrics are preferably used. For example, in addition to wet nonwoven fabrics, resin-bonded dry nonwoven fabrics, thermal bonded dry nonwoven fabrics, spunbonded dry nonwoven fabrics, needle-punched dry nonwoven fabrics, water-jet punching dry nonwoven fabrics, or fast-spinning dry nonwoven fabrics, nonwoven fabrics made by a papermaking method that can make the unit area weight and thickness uniform can also be preferably used. Among them, from the viewpoint of being located in a place in contact with human skin, thermal bonded dry nonwoven fabrics with excellent touch are preferably used as the surface sheet.

[0092] In addition, as the back sheet used when the absorbent of the present invention is made into a sanitary material product, from the viewpoint that the water vapor accumulated in the sanitary material product inside can be released to the outside and give the wearer comfort and the viewpoint that waterproofness and touch are excellent, it is preferably a laminated sheet of a moisture-permeable waterproof film and a nonwoven fabric. As the above-mentioned moisture-permeable waterproof film, porous polyethylene film, moisture-permeable polyurethane film or moisture-permeable polyester elastomer film etc. can be enumerated. In addition, as the above-mentioned nonwoven fabric, the nonwoven fabric same as the surface sheet can be used, but from the viewpoint of cost and intensity, it is preferably a spunbond dry nonwoven fabric.

[0093] Example

[0094] Hereinafter, the present invention will be described in detail based on Examples, but the present invention is not limited thereto. In addition, the performance in the Examples was measured by the following methods.

[0095] [Measurement method]

[0096] (1) Fiber content of nonwoven fabrics

[0097] Based on JIS L 1030-1 (2012) "Test method for mixing ratio of fiber products - Part 1: Fiber identification" and JIS L 1030-2 (2012) "Test method for mixing ratio of fiber products - Part 2: Fiber mixing ratio", the common mixing ratio (mass ratio of each fiber under standard conditions) is measured and used as the content (mass %) of the fibers constituting the nonwoven fabric.

[0098] (2) Weight per unit area of ​​nonwoven fabric

[0099] Based on JIS L1913 (2010) 6.2, the sample per unit area (1m 2 ) mass (g / m 2 ).

[0100] (3) Three-dimensional arithmetic roughness of nonwoven fabrics

[0101] Using a 3D shape measuring machine (KEYENCE, VR-3200), the three-dimensional arithmetic mean roughness (μm) of one side and the other side of each test piece was measured for 10 test pieces by the evaluation method specified in ISO 25178 (2010). Then, the average value of the measured values ​​of the obtained 20 points was calculated as the three-dimensional arithmetic mean roughness (μm) of the present invention. In the determination of the three-dimensional arithmetic mean roughness (μm), a 12-fold magnification (low magnification camera) was used, the mode was set to fine mode (finemode), and the filter processing setting was to set the filter type to "Gaussian", the S-filter to "none", the F-operation to "none", the L-filter to "none", and the terminal effect correction to "ON".

[0102] (4) Single fiber strength of short fibers

[0103] According to JIS L1015 (2010) 8.7.1, the single fiber strength is measured. Specifically, while a fiber is slowly stretched, both ends of the fiber are attached to paper with an adhesive, and a sample is prepared in which the portion attached with paper is used as the gripping portion. At this time, the area of ​​the fiber between the gripping portions alone is ensured to be 20 mm. The gripping portion of the sample is mounted on the clamp of a tensile tester (Tensilon universal testing machine model RTG-1210 manufactured by ORIENTEC), and stretched at a clip spacing of 10 mm and a tensile speed of 10 mm / min. The maximum load in the resulting elongation (mm)-load (N) curve is recorded as the single fiber strength (N). The measurement is performed on 10 samples of each type, and the average value is calculated.

[0104] (5) Weight per unit area of ​​water-absorbing polymer group

[0105] Ten samples (10 cm x 10 cm) of absorbent bodies were left to stand for more than 24 hours under standard conditions, and the water-absorbent polymer was collected from the water-absorbent polymer group of each sample. Next, the mass (g) of each sample under standard conditions was weighed to determine the mass per 1 m 2 Mass (g / m 2 ), and the average value of 10 pieces was calculated as the unit area weight (g / m 2 ).

[0106] (6) Saturated absorption capacity of water-absorbing polymer

[0107] The saturated absorption capacity was measured according to the tea bag method specified in JIS K 7223 (1996). The test liquid was set to physiological saline (0.90 mass % sodium chloride aqueous solution), and the immersion time was set to 24 hours. The tea bags (5 pieces) containing each sample were measured, and the average value was calculated as the saturated absorption capacity (g / g) of the water-absorbing polymer. It should be noted that the temperature of the physiological saline and the measurement atmosphere used was 25±2°C.

[0108] (7) Gel flow rate of water-absorbing polymer

[0109] 0.05 g of the sample was immersed in 150 ml of physiological saline (0.90 mass % sodium chloride aqueous solution) for 30 minutes to prepare hydrogel particles. Next, a metal mesh (mesh size 106 μm) was placed at the bottom of a vertically erected cylinder (inner diameter: 25.4 mm, length 56 cm, with scale marks at the position of 40 ml and 60 ml from the bottom) and the prepared hydrogel particles were transferred together with the physiological saline in a state where the stopcock was closed. A circular metal mesh (mesh size 150 μm) was placed on the hydrogel particles in a manner such that a pressure shaft (weight 58.5 g, length 70 cm) vertically bonded to the metal surface was placed on the hydrogel particles in a manner such that the metal mesh and the hydrogel particles were in contact. Next, a weight (50.5 g) was placed on the pressure shaft and left to stand for 1 minute. Next, the stopcock was opened, and the time (T: seconds) required for the liquid level in the filter cylinder to change from the 60 ml mark to the 40 ml mark was measured, and the gel flow rate (ml / min) in the present invention was calculated by the following formula. It should be noted that the temperature of the physiological saline solution and the measurement atmosphere used was 25±2°C.

[0110] Gel flow rate (ml / min) = 20ml x 60 / T seconds

[0111] (8) Particle size of water-absorbing polymer

[0112] A tray and sieves with nominal mesh sizes of 106 μm, 212 μm, 300 μm, 425 μm, 500 μm, 1 mm (1000 μm) and 1.4 mm according to JIS Z8801 were stacked in order from the bottom, 5.00 g of a water-absorbent polymer was placed on the 1.4 mm sieve, and an automatic shaker (AS ONE horizontal rotary sieve SKH-01) was used to shake the sieve at a scale setting of 3 for 10 minutes, and the presence and mass of the water-absorbent polymer on each sieve and tray were confirmed. However, when the water-absorbent polymer that could be confirmed to be present on each sieve or tray was less than 5% of the loading amount of 5.00 g, it was considered that there was no water-absorbent polymer on the sieve or tray.

[0113] Based on the obtained results, regarding the upper limit of the particle size of the water-absorbent polymer, the mesh size of the sieve with the largest mesh size among the sieves in which the water-absorbent polymer is confirmed to be present in an amount of 5% or more of the loading amount of 5.00 g is set as the upper limit of the particle size of the water-absorbent polymer. For example, when the sieve with the largest mesh size among the sieves in which the water-absorbent polymer is confirmed to be present in an amount of 5% or more of the loading amount of 5.00 g is a sieve with a mesh size of 425 μm, 500 μm, which is one step larger than the mesh size of the sieve, is set as the upper limit of the particle size of the water-absorbent polymer, and the particle size of the water-absorbent polymer is set to be 500 μm or less.

[0114] In addition, regarding the lower limit, the mesh size of the sieve with the smallest mesh size among the sieves in which the water-absorbent polymer is confirmed to exist in an amount of 5% or more of the loading amount of 5.00 g is used as the lower limit of the particle size of the water-absorbent polymer. It should be noted that when the water-absorbent polymer passes through a sieve with a mesh size of 106 μm and is also confirmed in an amount of 5% or more of the loading amount of 5.00 g in the tray, the tray is regarded as a sieve with a mesh size of 0 μm. For example, when the sieve with the smallest mesh size among the sieves in which the water-absorbent polymer is confirmed to exist in an amount of 5% or more of the loading amount of 5.00 g is a sieve with a mesh size of 106 μm, as a result of sieving the water-absorbent polymer, 106 μm is used as the lower limit of the particle size of the water-absorbent polymer, and the particle size of the water-absorbent polymer exceeds 106 μm.

[0115] (9) Liquid diffusion area

[0116] Liquid diffusivity was measured for 5 samples using a liquid permeability tester (manufactured by Lenzing Instruments, model: LISTER AC). More specifically, filter paper (manufactured by Nippon Paper CRECIA, absorbent paper folded four times), a metal mesh (mesh size 1.5 mm), and a sample (10 cm × 10 cm) were placed in order from the bottom at the sample setting position of the tester. It should be noted that the surface of the sample in contact with the metal mesh is the surface on the first non-woven fabric side in the first layer of the absorbent of the present invention, the surface on the second absorbent polymer side when the absorbent is made in the second non-woven fabric, and the surface on the third non-woven fabric side in the second layer. Next, 5 ml of physiological saline (0.90 mass % sodium chloride aqueous solution colored with blue dye) was put into the liquid inlet on the upper part of the tester, and the test was started. Then, 5 ml of physiological saline was dripped onto the surface of the sample, and the end of the liquid permeation was detected by the liquid permeation detection plate and liquid permeation detection electrode of the tester. Then, within 5 seconds after the completion of the liquid flow, a photograph was taken in such a way that the portion of the sample that turned blue by the physiological saline and the scale of the ruler were included in the same photograph. The area (cm2) of the portion that turned blue was calculated by relative comparison based on the scale of the ruler in the photograph. 2Then, the average of the areas of the five samples was calculated as the liquid diffusion area (cm 2 ). It should be noted that the temperature of the physiological saline solution and the measurement atmosphere used was 25±2°C.

[0117] (10)Thickness of absorber

[0118] The thickness of the sample was measured using a thickness gauge (constant pressure thickness gauge manufactured by TECLOCK, Model: PG11J) in accordance with JIS L1913 (1998) 6.1.2A. The thickness of each test piece (5 pieces) was measured and the average value was calculated as the thickness (mm) of the absorbent body.

[0119] (11) Absorption capacity of absorber

[0120] According to the order of back sheet and absorbent (sample), it is fixed on a stainless steel tilting table with an inclination angle of 45°. It should be noted that the sample is fixed in a stretched state in a manner consistent with the inclination direction in the length direction, in a manner in which the surface of the third nonwoven fabric side contacts the back sheet, and in order to eliminate wrinkles. Here, a porous polyethylene film is used for the back sheet. Then, at a position 1 cm below the upper end of the sample, a physiological saline solution (a 0.90 mass % sodium chloride aqueous solution is colored with a blue dye) prepared in advance in a beaker is dripped from a microtube pump at a speed of 1.5 g / sec, and the physiological saline solution is continued to be dripped until leakage of the physiological saline solution is observed from the lower end face of the sample. In more detail, 500 g of physiological saline solution is prepared in a beaker, and physiological saline solution is dripped in the above-mentioned inclination state, and the dripping is stopped at the moment when leakage of the physiological saline solution is observed from the lower end face of the sample. The weight (g) of the physiological saline solution that is not dripped and remains in the beaker is measured, and the absorption amount of the absorbent is calculated by the following formula. The physiological saline solution and the measurement atmosphere used had a temperature of 25±2°C.

[0121] Absorption of absorber (g) = 500g-Q

[0122] Q(g): The amount of saline remaining in the beaker without being added

[0123] In addition, the higher the value of the absorption amount is, the more excellent the liquid leakage prevention property is.

[0124] (12) Comprehensive evaluation

[0125] The obtained absorbent body was comprehensively evaluated according to the following criteria.

[0126] A: The absorption amount is 150 g or more, and the thickness is 4.0 mm or less.

[0127] B: The absorption amount is 125 g or more, and the thickness is 4.0 mm or less.

[0128] C: Satisfies at least one of the following conditions: absorption amount is less than 125 g, and thickness exceeds 4.0 mm.

[0129] [Example 1]

[0130] (No. 1 nonwoven fabric)

[0131] Short fibers (fiber diameter: 13 μm, fiber length: 51 mm, single fiber strength: 0.04 N) made of rayon were opened by carding and then formed into a web machine with a weight of 20 g / m 2 In addition, 70% by weight of the staple fibers formed of rayon and 30% by weight of hollow staple fibers formed of polyethylene terephthalate (fiber diameter: 30 μm, fiber length: 51 mm, single fiber strength: 0.30 N, hereinafter sometimes referred to as "short fibers A") were mixed by combing and opened, and then formed into a web with a unit area weight of 20 g / m 2 The parallel web and the cross web were overlapped (crisscrossed web), high pressure water was applied from the cross web side to entangle it, and dried at 150°C for 3 minutes, thereby obtaining a weight per unit area of ​​40 g / m 2 The first nonwoven fabric a of the spunlace nonwoven fabric is a spunlace nonwoven fabric. It should be noted that the ratio of the short fibers A contained in the first nonwoven fabric a is 15% by mass relative to the entire first nonwoven fabric a. In addition, the ratio of the short fibers formed of rayon contained in the first nonwoven fabric a is 85% by mass relative to the entire first nonwoven fabric a.

[0132] (No. 2 nonwoven fabric)

[0133] Short fibers (fiber diameter: 13 μm, fiber length: 51 mm, single fiber strength: 0.04 N) made of rayon were opened by carding and then formed into a web machine with a unit area weight of 15 g / m 2 Parallel web and unit area weight 15g / m 2 The parallel web and the cross web were overlapped, high pressure water was applied to entangle them, and dried at 150°C for 3 minutes, thereby obtaining a weight per unit area of ​​30 g / m 2 The spunlace nonwoven fabric is a second nonwoven fabric.

[0134] (No. 3 nonwoven fabric)

[0135] The same nonwoven fabric as the second nonwoven fabric was used.

[0136] (Absorber)

[0137] The parallel web side of the first nonwoven fabric was made the first surface, and the first surface was made into a 2 g / m 2The styrene hot melt was sprayed in a spraying manner, and the first water-absorbing polymer (NS300 manufactured by SDP GLOBAL) was uniformly sprayed thereon so that the weight per unit area became 100 g / m 2 Next, a second nonwoven fabric is placed on one side and pressed. Next, a third nonwoven fabric is placed on one side to form a 2 g / m 2 The styrene-based hot melt was sprayed in a spraying manner, and the second water-absorbing polymer (SA60S manufactured by Sumitomo Seika Chemicals) was uniformly sprayed thereon so that the weight per unit area became 150 g / m 2 . Next, the other side of the second nonwoven fabric (the side opposite to the side on which the first water-absorbent polymer is spread) is covered and crimped in such a way that it contacts the second water-absorbent polymer spread on the third nonwoven fabric. Here, the first water-absorbent polymer group is directly or indirectly fixed to the first nonwoven fabric. In addition, the second water-absorbent polymer group is directly or indirectly fixed to the third nonwoven fabric. A rectangular absorbent body is obtained by cutting the obtained material into a rectangle with a long side of 20 cm and a short side of 10 cm. The structure and performance of the absorbent body are shown in Table 1. The absorbent body has a thickness of 2.0 mm and an absorption capacity of 175 g. It is thin and has excellent absorption characteristics.

[0138] [Example 2]

[0139] (No. 1 nonwoven fabric)

[0140] Short fibers (fiber diameter: 13 μm, fiber length: 51 mm, single fiber strength: 0.04 N) made of rayon were opened by carding and then formed into a web machine with a unit area weight of 10 g / m 2 In addition, the staple fibers 40% by mass of the rayon and 60% by mass of the staple fibers A were mixed by combing, opened, and formed into a parallel web with a unit area weight of 10 g / m 2 The parallel web and the cross web were overlapped (crisscrossed web), high pressure water was applied from the cross web side to entangle it, and dried at 150°C for 3 minutes, thereby obtaining a weight per unit area of ​​20 g / m 2 The first nonwoven fabric b of the spunlace nonwoven fabric is a spunlace nonwoven fabric. It should be noted that the ratio of the short fibers A contained in the first nonwoven fabric b is 30% by mass relative to the entire first nonwoven fabric b. In addition, the ratio of the short fibers formed of rayon contained in the first nonwoven fabric b is 70% by mass relative to the entire first nonwoven fabric b.

[0141] (Absorber)

[0142] In addition to changing the first nonwoven fabric to the first nonwoven fabric b, the weight per unit area of ​​the first water-absorbing polymer was changed to 125 g / m 2The absorbent body was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent body are shown in Table 1. The absorbent body had a thickness of 1.9 mm and an absorption capacity of 160 g, and was thin and excellent in absorption characteristics.

[0143] [Example 3]

[0144] (No. 1 nonwoven fabric)

[0145] Short fibers (fiber diameter: 13 μm, fiber length: 51 mm, single fiber strength: 0.04 N) made of rayon were opened by carding and then formed into a web machine with a weight of 25 g / m 2 In addition, 80% by weight of the staple fibers formed by rayon and 20% by weight of the staple fibers formed by staple fibers A were mixed by combing, opened, and formed into a parallel web with a unit area weight of 25 g / m 2 The parallel web and the cross web were overlapped (crisscrossed web), high pressure water was applied from the cross web side to entangle it, and dried at 150°C for 3 minutes, thereby obtaining a weight per unit area of ​​50 g / m 2 The first nonwoven fabric c is a spunlace nonwoven fabric. The ratio of the short fibers A contained in the first nonwoven fabric c is 10% by mass relative to the entire first nonwoven fabric c. In addition, the ratio of the short fibers composed of rayon contained in the first nonwoven fabric c is 90% by mass relative to the entire first nonwoven fabric c.

[0146] (No. 2 nonwoven fabric)

[0147] Short fibers (fiber diameter: 13 μm, fiber length: 51 mm, single fiber strength: 0.04 N) made of rayon were opened by carding and then formed into a web machine with a weight of 22.5 g / m 2 Parallel web and unit area weight 22.5g / m 2 The parallel web and the cross web were overlapped, entangled by applying high pressure water flow, and dried at 150°C for 3 minutes, thereby obtaining a weight per unit area of ​​45 g / m 2 The spunlace nonwoven fabric is the second nonwoven fabric c.

[0148] (Absorber)

[0149] In addition to changing the first nonwoven fabric to the first nonwoven fabric c, changing the second nonwoven fabric to the second nonwoven fabric c, and changing the weight per unit area of ​​the first water-absorbing polymer to 75 g / m 2 The absorbent body was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent body are shown in Table 1. The absorbent body had a thickness of 2.2 mm and an absorption capacity of 150 g, and was thin and excellent in absorption characteristics.

[0150] [Example 4]

[0151] (No. 3 nonwoven fabric)

[0152] Short fibers (fiber diameter: 13 μm, fiber length: 51 mm, single fiber strength: 0.04 N) made of rayon were opened by carding and then formed into a web machine with a weight of 25 g / m 2 Parallel web and unit area weight 25g / m 2 The parallel web and the cross web were overlapped, entangled by applying high pressure water flow, and dried at 150°C for 3 minutes, thereby obtaining a weight per unit area of ​​50 g / m 2 The spunlace nonwoven fabric is the third nonwoven fabric d.

[0153] (Absorber)

[0154] The third nonwoven fabric was changed to the third nonwoven fabric d, the second water-absorbing polymer was changed to NS300 manufactured by SDP GLOBAL, and the weight per unit area of ​​the second water-absorbing polymer was changed to 125 g / m 2 The absorbent body was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent body are shown in Table 1. The absorbent body had a thickness of 2.1 mm and an absorption capacity of 150 g, and was thin and excellent in absorption characteristics.

[0155] [Example 5]

[0156] (No. 3 nonwoven fabric)

[0157] 70% by mass of staple fibers (fiber diameter: 13 μm, fiber length: 51 mm, single fiber strength: 0.04 N) composed of rayon and 30% by mass of staple fibers A were mixed by combing and opened to form a web with a weight of 10 g / m2 using a web forming machine. 2 Parallel web and unit area weight 10g / m 2 The parallel web and the cross web were overlapped, entangled by applying high pressure water flow, and dried at 150°C for 3 minutes, thereby obtaining a cross web with a unit area weight of 20 g / m 2 The 3rd nonwoven fabric of spunlace nonwoven fabric e.

[0158] (Absorber)

[0159] In addition to changing the third nonwoven fabric to the third nonwoven fabric e, the weight per unit area of ​​the second water-absorbing polymer was changed to 175 g / m 2 The absorbent body was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent body are shown in Table 1. The absorbent body had a thickness of 2.0 mm and an absorption capacity of 160 g, and was thin and excellent in absorption characteristics.

[0160] [Example 6]

[0161] In addition to changing the unit area weight of the second nonwoven fabric to 20g / m 2 The absorbent body was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent body are shown in Table 2. The absorbent body had a thickness of 1.9 mm and an absorption capacity of 150 g, and was thin and excellent in absorption characteristics.

[0162] [Example 7]

[0163] In addition to changing the unit area weight of the second nonwoven fabric to 50g / m 2 The absorbent was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent are shown in Table 2. The absorbent had a thickness of 2.2 mm and an absorption capacity of 160 g, and was thin and excellent in absorption characteristics.

[0164] [Example 8]

[0165] In addition to changing the unit area weight of the second nonwoven fabric to 15g / m 2 The absorbent was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent are shown in Table 2. The absorbent had a thickness of 1.8 mm and an absorption capacity of 140 g, and was thin and excellent in absorption characteristics.

[0166] [Example 9]

[0167] In addition to changing the unit area weight of the second nonwoven fabric to 60g / m 2 The absorbent was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent are shown in Table 2. The absorbent had a thickness of 2.3 mm and an absorption capacity of 145 g, and was thin and excellent in absorption characteristics.

[0168] [Example 10]

[0169] An absorbent was obtained in the same manner as in Example 1 except that the ratio of the short fibers A contained in the first nonwoven fabric was changed to 5% by mass relative to the entire first nonwoven fabric, and the ratio of the short fibers formed of rayon contained in the first nonwoven fabric was changed to 95% by mass relative to the entire first nonwoven fabric. The structure and performance of the absorbent are shown in Table 2. The absorbent had a thickness of 1.9 mm and an absorption capacity of 165 g, and was thin and excellent in absorption characteristics.

[0170] [Example 11]

[0171] An absorbent was obtained in the same manner as in Example 1 except that the ratio of the short fibers A contained in the first nonwoven fabric was changed to 40% by mass relative to the entire first nonwoven fabric, and the ratio of the short fibers formed of rayon contained in the first nonwoven fabric was changed to 60% by mass relative to the entire first nonwoven fabric. The structure and performance of the absorbent are shown in Table 2. The absorbent had a thickness of 2.2 mm and an absorption capacity of 150 g, and was thin and excellent in absorption characteristics.

[0172] [Example 12]

[0173] An absorbent was obtained in the same manner as in Example 1 except that the ratio of the short fibers formed of rayon contained in the first nonwoven fabric was changed to 100% by mass (without short fibers A) relative to the entire first nonwoven fabric. The structure and performance of the absorbent are shown in Table 3. The absorbent had a thickness of 1.8 mm and an absorption capacity of 135 g, and was thin and excellent in absorption characteristics.

[0174] [Example 13]

[0175] An absorbent was obtained in the same manner as in Example 1 except that the ratio of the short fibers A contained in the first nonwoven fabric was changed to 50% by mass relative to the entire first nonwoven fabric, and the ratio of the short fibers formed of rayon contained in the first nonwoven fabric was changed to 50% by mass relative to the entire first nonwoven fabric. The structure and performance of the absorbent are shown in Table 3. The absorbent had a thickness of 2.4 mm and an absorption capacity of 135 g, and was thin and excellent in absorption characteristics.

[0176] [Example 14]

[0177] In addition to changing the weight per unit area of ​​the first water-absorbing polymer to 50 g / m 2 The absorbent was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent are shown in Table 3. The absorbent had a thickness of 1.8 mm and an absorption capacity of 150 g, and was thin and excellent in absorption characteristics.

[0178] [Example 15]

[0179] In addition to changing the unit area weight of the first water-absorbing polymer to 25 g / m 2 The absorbent was obtained in the same manner as in Example 1. The structure and performance of the absorbent are shown in Table 3. The absorbent had a thickness of 1.7 mm and an absorption capacity of 135 g, and was thin and excellent in absorption characteristics.

[0180] [Example 16]

[0181] (No. 1 nonwoven fabric)

[0182] Short fibers (fiber diameter: 13 μm, fiber length: 51 mm, single fiber strength: 0.04 N) made of rayon were opened by carding and then formed into a web machine with a unit area weight of 15 g / m 2 In addition, the staple fibers 40% by mass of the rayon and 60% by mass of the staple fibers A were mixed by combing, opened, and formed into a parallel web with a unit area weight of 15 g / m 2 The parallel web and the cross web were overlapped (crisscrossed web), high pressure water was applied from the cross web side to entangle it, and dried at 150°C for 3 minutes, thereby obtaining a weight per unit area of ​​30 g / m 2 The first nonwoven fabric p is a spunlace nonwoven fabric. The ratio of the short fibers A contained in the first nonwoven fabric p is 30% by mass relative to the entire first nonwoven fabric p. In addition, the ratio of the short fibers composed of rayon contained in the first nonwoven fabric p is 70% by mass relative to the entire first nonwoven fabric p.

[0183] (Absorber)

[0184] An absorbent was obtained in the same manner as in Example 6 except that the first nonwoven fabric was changed to the first nonwoven fabric p. The structure and performance of the absorbent are shown in Table 3. The absorbent had a thickness of 1.8 mm and an absorption capacity of 135 g, and was thin and excellent in absorption characteristics.

[0185] [Example 17]

[0186] An absorbent was obtained in the same manner as in Example 7 except that the first nonwoven fabric was changed to the first nonwoven fabric p. The structure and performance of the absorbent are shown in Table 3. The absorbent had a thickness of 2.1 mm and an absorption capacity of 145 g, and was thin and excellent in absorption characteristics.

[0187] [Comparative Example 1]

[0188] In addition to changing the second nonwoven fabric to a hot air nonwoven fabric (made of polypropylene, with a unit weight of 50 g / m 2 The absorbent was obtained in the same manner as in Example 1 except that the thickness was 4.0 mm. The structure and performance of the absorbent are shown in Table 4. The absorbent had a thickness of 5.0 mm and an absorption capacity of 95 g, was bulky (thick), and had poor absorption properties.

[0189] [Comparative Example 2]

[0190] In addition to changing the second nonwoven fabric to a spunbonded nonwoven fabric (made of polypropylene, with a unit area weight of 10 g / m 2 ) was carried out in the same manner as in Example 1 to obtain an absorbent. The structure and performance of the absorbent are shown in Table 4. The absorbent had a thickness of 1.8 mm and an absorption capacity of 110 g. Although it was thin, its absorption characteristics were poor.

[0191] [Comparative Example 3]

[0192] In addition to changing the first nonwoven fabric to a spunbonded nonwoven fabric (made of polypropylene, with a unit area weight of 10 g / m 2 ) was carried out in the same manner as in Example 1 to obtain an absorbent. The structure and performance of the absorbent are shown in Table 4. The absorbent had a thickness of 1.8 mm and an absorption capacity of 60 g. Although it was thin, its absorption characteristics were poor.

[0193] [Comparative Example 4]

[0194] (No. 1 nonwoven fabric)

[0195] The first nonwoven fabric c was processed by calendering (cylinder pressure: 4 kgf / cm 2 , roll temperature: 20°C, speed: 1 m / min) to obtain a first nonwoven fabric ca.

[0196] (Absorber)

[0197] An absorbent was obtained in the same manner as in Example 1 except that the first nonwoven fabric was changed to the first nonwoven fabric ca. The structure and performance of the absorbent are shown in Table 4. The absorbent had a thickness of 1.8 mm and an absorption capacity of 50 g, and although it was thin, it had poor absorption characteristics.

[0198] [Comparative Example 5]

[0199] In addition to changing the third nonwoven fabric to a spunbonded nonwoven fabric (made of polypropylene, with a unit area weight of 10 g / m 2 ) was carried out in the same manner as in Example 1 to obtain an absorbent. The structure and performance of the absorbent are shown in Table 4. The absorbent had a thickness of 1.8 mm and an absorption capacity of 80 g. Although it was thin, its absorption characteristics were poor.

[0200] [Example 18]

[0201] In addition to changing the amount of hot melt sprayed on the first nonwoven fabric and the third nonwoven fabric to 4 g / m 2 The absorbent body was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent body are shown in Table 5. The absorbent body had a thickness of 1.9 mm and an absorption capacity of 160 g, and was thin and excellent in absorption characteristics.

[0202] [Example 19]

[0203] In addition to changing the amount of hot melt sprayed on the first nonwoven fabric and the third nonwoven fabric to 10 g / m 2 The absorbent was obtained in the same manner as in Example 1 except for the above. The structure and performance of the absorbent are shown in Table 5. The absorbent had a thickness of 1.7 mm and an absorption capacity of 130 g, and was thin and excellent in absorption characteristics.

[0204] [Example 20]

[0205] (No. 2 nonwoven fabric)

[0206] Short fibers (fiber diameter: 13 μm, fiber length: 51 mm, single fiber strength: 0.04 N) made of rayon were opened by carding and then formed into a web machine with a weight of 30 g / m 2 The obtained parallel web was entangled by applying high-pressure water flow and dried at 150°C for 3 minutes, thereby obtaining a parallel web with a unit area weight of 30 g / m 2 The spunlace nonwoven fabric is the second nonwoven fabric f.

[0207] (Absorber)

[0208] An absorbent was obtained in the same manner as in Example 1 except that the second nonwoven fabric and the third nonwoven fabric were respectively changed to the second nonwoven fabric f and the second water-absorbing polymer was changed to NS300 manufactured by SDP GLOBAL. The structure and performance of the absorbent are shown in Table 5. The absorbent had a thickness of 2.1 mm and an absorption capacity of 165 g, and was thin and excellent in absorption characteristics.

[0209]

[0210]

[0211]

[0212]

[0213]

Table 5

[0214]

[0215] 1) The ratio of the short fibers A having a single fiber strength of 0.15 N or more to the entire first nonwoven fabric

[0216] 2) The value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer

[0217] 3) The value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer

[0218] Here, the absorbents of Examples 1 to 20 are compared with the absorbents of Comparative Examples 1 to 2. The absorbents of Examples 1 to 20 are absorbents in which the second nonwoven fabric is composed only of hydrophilic fibers, whereas the absorbents of Comparative Examples 1 to 2 are absorbents in which the second nonwoven fabric is composed only of hydrophobic fibers. In addition, if we focus on the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer and the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer, the absorbents of Comparative Examples 1 to 2 are absorbents in which the liquid diffusion of the second nonwoven fabric is inferior to the liquid diffusion of the first and second layers, whereas the absorbents of Examples 1 to 20 are absorbents in which the liquid diffusion of the second nonwoven fabric is superior to the liquid diffusion of the first and second layers. Therefore, the absorption characteristics of the absorbents of Examples 1 to 20 are superior to the absorption characteristics of Comparative Examples 1 to 2. Furthermore, regarding the thickness of the absorbent body, it can be said that the absorbent bodies of Examples 1 to 20 are significantly thinner than the absorbent body of Comparative Example 1.

[0219] The absorbents of Examples 1 to 20 were compared with the absorbent of Comparative Example 3. If the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer is taken into consideration, the absorbent of Comparative Example 3 is an absorbent in which the liquid diffusion area of ​​the first layer is extremely small relative to the liquid diffusion area of ​​the second nonwoven fabric, whereas the absorbents of Examples 1 to 20 are absorbents in which the liquid diffusion area of ​​the first layer is appropriately small relative to the liquid diffusion area of ​​the second nonwoven fabric. Therefore, the absorption characteristics of the absorbents of Examples 1 to 20 are superior to the absorption characteristics of the absorbent of Comparative Example 3.

[0220] The absorbents of Examples 1 to 20 were compared with the absorbent of Comparative Example 4. If the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer is taken into consideration, the absorbent of Comparative Example 4 is an absorbent in which the liquid diffusion area of ​​the second nonwoven fabric is inferior to the liquid diffusion area of ​​the first layer, whereas the absorbents of Examples 1 to 20 are absorbents in which the liquid diffusion area of ​​the second nonwoven fabric is superior to the liquid diffusion area of ​​the first layer. Therefore, the absorption characteristics of the absorbents of Examples 1 to 20 are superior to the absorption characteristics of the absorbent of Comparative Example 4.

[0221] The absorbents of Examples 1 to 20 were compared with the absorbent of Comparative Example 5. If the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer is taken into consideration, the absorbent of Comparative Example 5 is an absorbent in which the liquid diffusion area of ​​the second layer is extremely small relative to the liquid diffusion area of ​​the second nonwoven fabric, whereas the absorbents of Examples 1 to 20 are absorbents in which the liquid diffusion area of ​​the second layer is appropriately small relative to the liquid diffusion area of ​​the second nonwoven fabric. Therefore, the absorption characteristics of the absorbents of Examples 1 to 20 are superior to the absorption characteristics of the absorbent of Comparative Example 5.

[0222] Next, the absorbent of Example 1 was compared with the absorbent of Example 2. The liquid diffusion area of ​​the first layer of the absorbent of Example 1 was larger than the liquid diffusion area of ​​the first layer of the absorbent of Example 2. In addition, the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer was moderately smaller in the absorbent of Example 1 than in the absorbent of Example 2. Therefore, the absorption characteristics of the absorbent of Example 1 were superior to those of the absorbent of Example 2.

[0223] The absorbent of Example 1 was compared with the absorbent of Example 3. The liquid diffusion area of ​​the first layer of the absorbent of Example 1 is appropriately smaller than that of the first layer of the absorbent of Example 3, and liquid leakage from the first layer can be further suppressed in the absorbent of Example 1. Therefore, the absorption characteristics of the absorbent of Example 1 are superior to those of the absorbent of Example 3.

[0224] The absorbent of Example 1 was compared with the absorbent of Example 4. The absorbent of Example 1 had a value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer which was appropriately larger than that of the absorbent of Example 4, and the liquid leakage from the second layer could be further suppressed in the absorbent of Example 1. Therefore, the absorption characteristics of the absorbent of Example 1 were superior to those of the absorbent of Example 4.

[0225] The absorbent of Example 1 was compared with the absorbent of Example 5. The absorbent of Example 1 had a value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer which was appropriately smaller than that of the absorbent of Example 5, and the liquid leakage from the second nonwoven fabric could be further suppressed in the absorbent of Example 1. Therefore, the absorption characteristics of the absorbent of Example 1 were superior to those of the absorbent of Example 5.

[0226] In addition, the absorbent of Example 1 was compared with the absorbents of Examples 16 to 17. The absorbents of Examples 16 to 17 were absorbents in which the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer was the same as the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer, whereas the absorbent of Example 1 was absorbent in which the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer was smaller than the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer. Therefore, the absorption characteristics of the absorbent of Example 1 were superior to those of the absorbents of Examples 16 to 17.

[0227] In addition, the absorbent of Example 1 was compared with the absorbents of Examples 18 to 19. The amount of adhesive applied to each of the first layer and the second layer of the absorbent of Example 1 is appropriately smaller than that of the absorbents of Examples 18 to 19. The liquid diffusion area of ​​the first layer of the absorbent of Example 1 is appropriately larger than that of the first layer of the absorbents of Examples 18 to 19, and the absorption amount of urine, etc. of the water-absorbing polymer of the first layer and the first nonwoven fabric itself can be increased in the absorbent of Example 1. In addition, the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer of the absorbent of Example 1 is appropriately smaller than that of the absorbents of Examples 18 to 19. In addition, the value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer of the absorbent of Example 1 is appropriately smaller than that of the absorbents of Examples 18 to 19. Therefore, the absorption characteristics of the absorbent of Example 1 are superior to those of the absorbents of Examples 18 to 19.

[0228] Industrial Applicability

[0229] The absorbent of the present invention is an absorbent having excellent absorption properties and can be suitably used as various sanitary products such as tape-type diapers, pants-type diapers, sanitary napkins, and urine absorbing pads.

Claims

1. An absorbent body comprising, in order, a first nonwoven fabric, a first water-absorbing polymer group, a second nonwoven fabric, a second water-absorbing polymer group, and a third nonwoven fabric, wherein the absorbent body has a thickness of 4.0 mm or less, The first nonwoven fabric and the first water-absorbing polymer group form a first layer, The third nonwoven fabric and the second water-absorbing polymer group form a second layer, The first water-absorbing polymer group is directly or indirectly fixed to the first nonwoven fabric, The second water-absorbing polymer group is directly or indirectly fixed to the third non-woven fabric, The second nonwoven fabric contains 60% by mass or more of hydrophilic fibers relative to the entire second nonwoven fabric. The liquid diffusion area of ​​the first layer is 40 to 90 cm 2 , The value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the first layer is 1.1 to 2.0, The value obtained by dividing the liquid diffusion area of ​​the second nonwoven fabric by the liquid diffusion area of ​​the second layer is 1.1 to 2.

5.

2. The absorbent body according to claim 1, wherein The hydrophilic fiber is rayon fiber.

3. The absorbent body according to claim 1 or 2, wherein: The second nonwoven fabric has a unit area weight of 20 to 50 g / m 2 .

4. The absorbent body according to any one of claims 1 to 3, wherein The first nonwoven fabric comprises short fibers A having a single fiber strength of 0.15 N or more, The content of the short fibers A is 5 to 40% by mass based on the entire first nonwoven fabric.

5. The absorbent body according to any one of claims 1 to 4, wherein The first water-absorbing polymer group has a unit area weight of 50 to 400 g / m 2 .

6. The absorbent core according to any one of claims 1 to 5, wherein The saturated absorption capacity of the water-absorbing polymer contained in the second water-absorbing polymer group is 25 to 70 g / g.

7. A sanitary product comprising the absorbent body according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Water absorbent sheet, water absorbent sheet production method, and absorbent article

    WO2019198821A1